2007
DOI: 10.1197/j.aem.2006.09.053
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between a Clear‐cut Alternative Noncardiac Diagnosis and 30‐day Outcome in Emergency Department Patients with Chest Pain

Abstract: In the ED chest pain patient, the presence of a clear-cut alternative noncardiac diagnosis reduces the likelihood of a composite outcome of death and cardiovascular events within 30 days. However, it does not reduce the event rate to an acceptable level to allow ED discharge of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…This accounts for more than 50% of patients with acute chest pain 11,12 and is typical of broad based ED chest pain patient populations that have only a 5% to 20% risk of an ACS. 3,[5][6][7][8][11][12][13][14] Coronary CTA has high diagnostic accuracy. Janne d'Othee et al, 21 in a meta-analysis of 41 trials with over 2,500 patients, found a sensitivity of 95% and specificity of 85% relative to cardiac catheterization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This accounts for more than 50% of patients with acute chest pain 11,12 and is typical of broad based ED chest pain patient populations that have only a 5% to 20% risk of an ACS. 3,[5][6][7][8][11][12][13][14] Coronary CTA has high diagnostic accuracy. Janne d'Othee et al, 21 in a meta-analysis of 41 trials with over 2,500 patients, found a sensitivity of 95% and specificity of 85% relative to cardiac catheterization.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13] Although clinical algorithms can successfully risk stratify patients, they have not typically been considered useful in identifying a group of patients with a 30-day 1% risk for an adverse event who can safely be discharged from the ED. [2][3][4][5][6][7][8][9][10][11][12][13][14] Coronary computerized tomographic angiography (CTA) has been shown to have excellent diagnostic accuracy when compared to cardiac catheterization [15][16][17][18][19][20][21] and appears to perform as well as myocardial perfusion imaging in identifying patients at low risk for cardiovascular events. [22][23][24][25][26] Observational studies of coronary CTA have found that patients with normal coronary CTA results are at low risk for adverse events over 1-2 years; however, these studies either were small or involved patients who had other standard assessments to aid in clinical management.…”
mentioning
confidence: 99%
“…8 The majority ultimately will be found not to have ACS, but symptoms caused by noncardiac and often benign disorders such as musculoskeletal pain, pleuritis, or gastroesophageal reflux make the rapid rule-out of ACS more difficult and result in huge medical expenses. Safe and early rule-out of ACS contributes to more efficient and high-value healthcare delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Although the recognition of patients at high risk of ACS has improved steadily, identifying the majority of chest pain presentations who fall into the low‐risk group remains a challenge 5,6 . The process of assessing patients in the ED with possible ACS remains time‐consuming and is not without controversy.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Although the recognition of patients at high risk of ACS has improved steadily, identifying the majority of chest pain presentations who fall into the low-risk group remains a challenge. 5,6 The process of assessing patients in the ED with possible ACS remains time-consuming and is not without controversy. Many key questions remain unanswered, such as the role of accelerated biomarker risk stratification as early as 2 h following ED presentation, the added value of multiple biomarker assays including change in their absolute levels (delta values) and the clinical utility of early (within 72 h) provocation testing such as an exercise ECG, particularly in patients under 40 years of age without risk factors who present with normal serial ECG and biomarkers (see Discussion).…”
Section: Introductionmentioning
confidence: 99%